2021
DOI: 10.1177/02692155211009484
|View full text |Cite
|
Sign up to set email alerts
|

Educating caregivers of persons with cerebral palsy in night-time postural care: A randomized trial comparing two online training programs

Abstract: Objective: Compare effectiveness of two differently formatted training programs in educating night-time postural care implementers. Design: Mixed-methods parallel-group double-blind design with random assignment. Setting: United States academic institution. Participants: Thirty-eight adult caregivers/providers of children with cerebral palsy. Interventions: Both 2-hour online programs included content on night-time postural care evidence, risk-factor monitoring, sleep-system types, positioning methods, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(34 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…1725 Two articles examine the current postural care training needs for clinical practice. 9,11 Two articles describe the development or effectiveness of a postural care training program for parents, school staff, and nurses. 26–27 Two examine and evaluate specific postural care training programs intended for both parents and rehabilitation professionals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1725 Two articles examine the current postural care training needs for clinical practice. 9,11 Two articles describe the development or effectiveness of a postural care training program for parents, school staff, and nurses. 26–27 Two examine and evaluate specific postural care training programs intended for both parents and rehabilitation professionals.…”
Section: Resultsmentioning
confidence: 99%
“…9–11,27,28 Two of these studies were descriptive/exploratory in which both caregivers and multidisciplinary team members reported dissatisfaction and a lack of overall knowledge due to the amount of postural care training they received. 9,11 Another study identified knowledge differences that occur across disciplines such that nurses and occupational therapists reported having more knowledge than speech therapists and psychologists. 9 One single-subject design and one experimental study showed that that postural care training programs for parents and teachers have a positive impact, but parents and teachers may need additional training compared to professionals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations